2000
DOI: 10.1063/1.373506
|View full text |Cite
|
Sign up to set email alerts
|

Minority carrier lifetime and iron concentration measurements on p-Si wafers by infrared photothermal radiometry and microwave photoconductance decay

Abstract: A comparative study of electronic transport properties of p-Si wafers intentionally contaminated with Fe was performed using infrared photothermal radiometry (PTR) and microwave photoconductance decay (µ-PCD). Strong correlations were found between PTR and µ-PCD lifetimes in a lightly contaminated wafer with no significant PTR transient behavior. The absolute PTR lifetime values were larger than the local averaged µ-PCD values, due to the different excitation wavelengths and probe depths. In a heavily contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…3 The system has been modified to include a tunable titanium:sapphire ͑Ti:Sa͒ laser capable of operating over the wavelength range of 690-1100 nm whose emissions are monitored by a wavemeter with less than 0.1 nm resolution. An argon ion laser is used to pump the Ti:Sa laser or the Ti:Sa can be bypassed so that the Ar ϩ emission can be focused directly on the sample to perform experiments with 514 nm excitation.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…3 The system has been modified to include a tunable titanium:sapphire ͑Ti:Sa͒ laser capable of operating over the wavelength range of 690-1100 nm whose emissions are monitored by a wavemeter with less than 0.1 nm resolution. An argon ion laser is used to pump the Ti:Sa laser or the Ti:Sa can be bypassed so that the Ar ϩ emission can be focused directly on the sample to perform experiments with 514 nm excitation.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Iron mapping based on infrared photothermal radiometry has also been recently developed. 20 All of these techniques rely on the underlying principle initially developed by Zoth and Bergholz, 12 who showed that the interstitial iron concentration ͓Fe i ͔ can be found via measurement of the carrier lifetime ͑or, equivalently, the diffusion length͒, before and after breaking FeB pairs in a borondoped p-type silicon sample. The iron concentration is determined by 10,12 ͓Fe…”
Section: Existing Iron Mapping Techniquesmentioning
confidence: 99%
“…1 It was derived from the well-known infrared photothermal radiometry ͑PTR͒, a technique extensively used in semiconductor analysis. [2][3][4][5][6] Both techniques rely on the measure of infrared radiation from an optically excited region of the sample. When a semiconductor is optically excited by an intensity modulated laser beam with photon energy h greater than the fundamental energy gap E g , absorption will occur, and a net amount of free carriers will be generated, in addition to the existing intrinsic carrier density.…”
Section: ͑Received 24 February 2003; Accepted 14 April 2003͒mentioning
confidence: 99%